Phylogenetic diversity patterns of woody species across different tree sizes and spatial scales in a tropical forest community on Con Dao Islands - Van Quy, Nguyen; Manh, Vu; Tuan Minh Thanh, Doan; Thi Van, Nguyen; Trung Duc, Nguyen; Hong Hai, Nguyen (Journal of Forestry Science and Technology, 2024)
Understanding the maintenance of diversity and the assembly of communities is a primary concern in community ecology. This study explored the phylogenetic structure of an evergreen broadleaved tree community in Con Dao National Park, Vietnam. The survey, conducted in December 2023, encompassed all tree individuals with a diameter at breast height (DBH) ≥ 2.5 cm within a 4-ha study plot. These individuals were identified by species name, and their DBH was measured. Subsequently, a community phylogenetic tree was constructed using the Phylomatic online platform. The 4-ha study plot was subdivided into there different subplots based on three spatial scales (25 m × 25 m, 50 m × 50 m, and 100 m × 100 m) and all trees were classified into three different DBH classes (2.5 cm ≤ DBH < 10 cm representing small trees; 10 cm ≤ DBH < 20 cm as medium trees; and DBH ≥ 20 cm as large trees). The net relatedness index (NRI) and net nearest taxon index (NTI) were utilized to evaluate the phylogenetic structure and infer ecological processes. Our findings revealed a consistent decrease in both NRI and NTI with increasing spatial scales and tree sizes. These results suggest an overdispersed phylogenetic structure within the community across different spatial scales and tree sizes. Additionally, negative density dependence was found to have a pronounced effect on the phylogenetic structure, with a more significant impact on tree individuals from small and medium DBH classes than large ones. This study underscores the significance of phylogenetic density dependence as a primary mechanism governing species diversity and shaping the community structure of evergreen broadleaved forests in Vietnam.